Uma reforma contra o funcionalismo - Silva, Leonardo Barbosa e [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
Este artigo analisa a proposta de reforma do Estado focada no funcionalismo público durante os dois mandatos de Fernando Henrique Cardoso, confirmando a perspectiva fiscalista presente nas reformas do século XX e a preservação de pontos históricos de deficiência do serviço público.

This article has as a goal to analyze the state reform aimed on civil service during both Fernando Henrique Cardoso's mandates, ratificating the fiscal perspective presents at the twentieth century reforms and in the preservation of historic issues on public services deficiency.
One reform against the functionalism
Keywords: Reforma do Estado; Ajuste fiscal; Funcionalismo público